Penggunaan Media Sosial X pada Akun @Txtdrberseragam untuk Mengetahui Tingkat Kepercayaan Masyarakat Yogyakarta terhadap Kepolisian RI - Razan Arvin Pradipa Wahyu; Angga Intueri Mahendra (MUKASI: Jurnal Ilmu Komunikasi, 2024)
The formulation in this study is how to use social media x on @txtdrberseragam accounts to find out the level of trust of the people of Yogyakarta towards the Indonesian Police. The purpose of this study is to find out the level of trust of the people of Yogyakarta in the Indonesian Police through the use of social media X @txtdrberseragam accounts. The research method used in this study is descriptive quantitative statistics. The data collection technique in this study was by distributing a questionnaire of 100 respondents taken from @txtdrberseragam account followers. The results of the study showed the categorization of the scale of Yogyakarta people's trust in the police regarding exposure to social media X content from @txtdrberseragam accounts, namely, 12% (12 people) were in the high category, then 71% (71 people) were in the medium category, and 17% (17 people) were in the low category. It can be stated that the level of trust of the people of Yogyakarta in the police about the exposure of social media content X from @txtdrberseragam accounts is in the medium category of 71%. Thus, that the use of social media X can be used to find out the level of trust of the people of Yogyakarta in the Indonesian Police. Then based on the results of the analysis, it was found that the trust of the people of Yogyakarta in the Indonesian Police increased from 2023-2024.